CRIMINAL ACT OF THEFT IN PENAL CODE PRESPECTIVE AND ISLAMIC LAW - Syafii, Ahmad (Tadulako Law Review, 2017)
Crime is regulated in Indonesian Criminal Code or positive law has been classified into several types of theft crimes, ranging from theft of ordinary crimes (Article 362 of the Criminal Code) punishable with imprisonment of five years, the crime of theft by weighting (Article 363 of the Criminal Code) punishable by a maximum imprisonment of seven years, minor theft crimes (Article 364 of the Criminal Code) punishable with imprisonment of three months, theft and violent crime (Article 365 of the Criminal Code) threatened with imprisonment of twelve years, the crime of theft in the family (Article 367 of the Criminal Code) is absolutely not possible prosecution. In Islamic criminal law, crime is known as jarimah. Jarimah is any Syara’ prohibition which had been threatened with had punishment or ta’zir. Therefore in jarimah theft included under Islamic criminal law may be using cut hands had punishment {Surah Al-Maidah (5): 38}. Had punishment by cut the and is applied when reaching a predetermined nishab, while ta’zir law done if not fulfilled the terms of theft that requires had punishment.